2003
DOI: 10.1159/000073936
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants: A Possible Role in Kidney Protection

Abstract: Oxidative stress contributes to the pathophysiology of kidney injury. Beneficial renal effects of some medications, such as angiotensin-converting enzyme inhibitors, angiotensin II type 1 receptor antagonists, calcium channel blockers, β-blockers and lipid lowering agents depend at least partially on the ability to alleviate oxidative stress. The administration of various natural or synthetic antioxidants has been shown to be of benefit in prevention and attenuation of renal scaring in numerous animal models o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 149 publications
(159 reference statements)
0
46
1
Order By: Relevance
“…Only individuals with impaired antioxidant defense, or those faced with conditions of oxidative stress, may benefit from antioxidant therapy. 34 We have noticed that the oxidative stress in RK rats after week 8, which was the end stage of RK, returned to normal, and the redox state in sham rats was also balanced. Under these conditions, giving antioxidant has deleterious effects.…”
Section: Discussionmentioning
confidence: 93%
“…Only individuals with impaired antioxidant defense, or those faced with conditions of oxidative stress, may benefit from antioxidant therapy. 34 We have noticed that the oxidative stress in RK rats after week 8, which was the end stage of RK, returned to normal, and the redox state in sham rats was also balanced. Under these conditions, giving antioxidant has deleterious effects.…”
Section: Discussionmentioning
confidence: 93%
“…24 N-acetylcysteine is an ideal candidate for replenishing tissue GSH levels through two major protective mechanisms: it acts as precursor for GSH synthesis (sulfhydryl source for GSH synthesis) 66 and nucleophile that scavenges reactive oxygen species such as O2 , H2O2 and OH 67 and conjugates with reactive metabolites rendering them less toxic. 68 The underlying mechanisms governing the tissue-specific effects of NAC on SOD protein expression might be due to tissue-specific effectiveness of NAC in reducing the production of superoxide.…”
Section: 50mentioning
confidence: 99%
“…20 It is a synthetic precursor of GSH, which can stimulate the intracellular synthesis of GSH and enhances glutathione S-transferase (GST) activity. 21 It is a small molecule that can be freely filtered, with easy access to intracellular compartments and is very effective in neutralizing free radicals intracellularly. 22,23 Studies using animals have confirmed renal protective effect of NAC in druginduced nephrotoxicity.…”
Section: Introductionmentioning
confidence: 99%